Chitosan and polyvinylpyrrolidone as potential biomaterials to develop antimalarial and antimicrobial drug delivery systems, encapsulating thiadiazines (bis-THTT), ecuadorian propolis and honey - Espinel Cadena, Pablo Sebastian (2024)
The development of drug delivery systems in the form of nanoparticles produced from biomaterials such as chitosan (CS) and polyvinylpyrrolidone (PVP) is of great importance in nanomedicine due to their advantageous properties such as biocompatibility, biodegradability and antimicrobial activity. In general, a large number of drugs have low solubility in water, which makes their absorption and therapeutic efficacy limited. The encapsulation of these compounds in nanoparticles can increase their solubility, which improves their bioavailability and therapeutic efficacy. This work presents the methodology to prepare chitosan (CS) and polyvinylpyrrolidone (PVP) nanoparticles that help release bis-THTT thiadiazines (JH1 and JH2) and natural products (honey and propolis) in a controlled and sustained manner over time, for therapeutic purposes. In this study, nanoparticles (NPs) with CS:PVP ratios of 1:0.5, 1:0.75, 1:1 and 1:1.25 were synthesized to determine the influence of this factor on their formation. Volumetric ratios of 1:0.5, 1:0.75, 1:1 and 1:1.25 of the 0.2% solution of these biopolymers with respect to the cross-linking agent (TPP) were tested, and the combination that allows an adequate synthesis of chitosan and PVP nanoparticles was determined. Thiadiazines JH1, JH2 that have previously demonstrated considerable antimalarial activity, and on the other hand honey and propolis, were encapsulated in CS-PVP nanoparticles and their antimicrobial activity against the strain E. coli ATCC 25922 was demonstrated through the disk diffusion method. The prepared NPs were characterized using FTIR, TGA, XRD and AFM techniques, which confirmed the loading of antimalarials and antimicrobials in them. The in vitro controlled release of antimalarials JH1 and JH2 and natural antimicrobials honey and propolis in artificial gastric fluid (AGF) at pH 1.78 was also demonstrated. Finally, the cytotoxicity of the nanoparticles was evaluated using the colorimetric MTT method of Promega Corporation at 5 and 10 μg/ml of nanoparticle concentration. The results indicated that the prepared NPs are not cytotoxic, therefore it is concluded that the prepared NPs can be used as drug delivery systems.